FAKTOR PENENTU RETURN SAHAM PERBANKAN: STUDI PROFITABILITAS SEBAGAI VARIABEL INTERVENING DI BURSA EFEK INDONESIA (2019-2022) - Ariyantiningsih, Febri (Relawan Jurnal Indonesia, 2024)
This study aims to analyze the effect of company size, working capital turnover, and sales growth on stock returns with profitability as an intervening variable in conventional banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The research method used is quantitative with multiple regression analysis and path analysis approaches. The results showed that company size and working capital turnover had a positive effect on profitability, while sales growth had no significant effect. Profitability acts as an intervening variable that strengthens the relationship between company size and working capital turnover on stock returns. However, sales growth has no significant effect on stock returns either directly or through profitability. These findings provide implications for investors in considering the fundamental factors of banking companies before making stock investments.